High-resolution electronic excitation and emission spectra of pentacene and 6,13-diazapentacene monomers and weakly bound dimers by matrix-isolation spectroscopy - Thusek, Jean; Hoffmann, Marvin; Hübner, Olaf; Germer, Stefan; Hoffmann, Hendrik; Freudenberg, Jan; Bunz, Uwe H. F.; Dreuw, Andreas; Himmel, Hans-Jörg (Chemistry - a European journal, 2021)
N-Heteropolycycles are among the most promising candidates for applications in organic devices. For this purpose, a profound understanding of the low-energy electronic absorbance and emission characteristics is of crucial importance. Herein, we report high-resolution absorbance and fluorescence spectra of pentacene (PEN) and 6,13-diazapentacene (DAP) in solid neon obtained using the matrix-isolation technique. Accompanying DFT calculations allow the assignment of specific vibrationally resolved signals to corresponding modes. Furthermore, we present for the first time evidence for the formation of van der Waals dimers of both substances. These dimers exhibit significantly different optical characteristics resulting from the change of electronic properties evoked by the incorporation of sp2 nitrogen into the molecular backbone.